Employing Barcode High-Resolution Melting Technique for Authentication of Apricot Cultivars - Kaan Hürkan (Journal of Agricultural Sciences)
Fast, accurate and affordable identification of food products is important to ensure authenticity and safety. There are various apricot (Prunus armeniaca L.) cultivars are being produced in Turkey. Each cultivar differs in quality and purpose of use. In this paper, we aimed to develop an easy and reliable method, Barcode High-Resolution Melting (Bar-HRM), to distinguish apricot cultivars. We designed and tested novel Bar-HRM primer sets HRM-ITS1 and HRM-ITS2, targeting the most popular barcoding region ITS1 and ITS2, specific to apricot cultivars. According to the results, HRM analysis distinguished 31 cultivars of 35 for ITS1, and 35 for ITS2. We recommend using ITS2 barcode region, amplified with using HRM-ITS2 primer set, for Bar-HRM analysis of different apricot cultivars.